RETARDATION OF VISUAL PERCEPTION AS A CRITERION FOR EARLY DETECTION OF DYSLEXIA - Olga М. Moshkova (Образование и наука)
Abstract. The research aim is to reveal diagnostics possibilities of incompleteness of subsequent visual scanning and holistic strategy of an identification of the visual cues affected on successful children reading skills formation. Methods. While working out the diagnostic methodology of deterioration of reading skills (dyslexia), the author relies on the ontogenetic principles (from simple to complicated), integrity, system approach and fundamental principles on common principles of speech development (B. G. Anan’ev, L. I. Beljakova, N. I. Zhinkin, A. A. Leont’ev, T. N. Ushakova). Besides the principles of specific pedagogics, the author uses general pedagogical principles as presentation, accessibility, consciousness, concretenesses, an individual approach, stage-by-stage skills formation, etc. The methods of direct application on defective activity and didactic information (selection and arrangement are considered). Results. The author specifies the characteristics of visual perception affected on successful reading skills acquirement of schoolchildren during the period of primary education due to the detection of suppositions to deterioration of their reading skills (dyslexia) and graded-correctional effect on them. The types of visual scanning or search such as consistent field of gaze fixation from left to right and the chaotic search presented with «spasmodic» returnable eye movements. Additionally, the strategies of a visual identification are defined: holistic (a complete identification of hierarchically organised visual cues) and analytical (element-by-element recognition). It is proved that in the course of training to reading children gradually go over from chaotic to the consecutive search necessary for right-hand visual scanning of the text; and from analytical strategy to holistic. Retardation of visual perception development (shown in absence of the given transition) causes occurrence of dyslexia. Scientific novelty. The author presents own developed and tested diagnostic methodology that allows finding out an underlying risk for dyslexia emergence; it is related to chaotic visual search and analytical strategy of an identification of printed characters. The traditional method of coping with the reading skills defect is updated with new methods and techniques of correctional actions which are directed at visual perception improvement. Practical significance. Proposed diagnostic methods can be used by speech therapists or speech-language pathologists of general education institutions for early detection and warning of the reading skills defect.